Vojtech Rihovsky and his Activities in Dub nad Moravou - Silna, Ingrid (Musicologica Olomucensia, 2013)
The paper deals with the youth of the composer Vojtech Rihovsky (1871-1950) and his work as an organist and choirmaster at the Purification of the Virgin Mary Church in Dub nad Moravou until 1902, when he moved to Chrudim. The paper describes his family background and music education in Prague. It also covers and briefly analyses his compositional output during that time and takes account of its contemporary success.
Keywords: Church music; 1860-1902; Dub nad Moravou; Purification of the Virgin Mary Church; choirmaster; organist; composer